Yield loss estimation in fennel (Foeniculum vulgare Mill.) due to root knot nematode - PATEL, D J PATEL, S K PATEL, H V (Journal of Spices and Aromatic Crops, 1995)
Meloidogyne javanica (patho type 3) is a serious pest of fennel (Foeniculum vulgare) in Gujarat and can cause up to 28 Per cent loss in grain yield. Application of carbofuran (Furadan 3 G) is effective in reducirig the nematode infestation.